Modulating taste and trigeminal sensations in food models to assess individual variations in sensory and hedonic responses to food - Angelica Lippi; Caterina Dinnella; Sara Spinelli; Agnès Giboreau; Véronique Mourier; Erminio Monteleone (Clinical Nutrition Open Science, 2024)
Summary: Background & Aims: Adoption and maintenance of healthy diets among vulnerable populations, such as cancer patients, can be challenging. The preliminary study of sensory-hedonic responses through the modulation of key sensory properties in food models in healthy participants, could contribute to explore a new method to answer to nutrition in cancer's issue. Sensory and hedonic responses are affected, among other factors, by sensory responsiveness and psychological traits.With the perspective of using the approach to investigate individual differences in sensory and hedonic responses in cancer patients undergoing chemotherapy experiencing taste alterations, two food models were designed and pre-tested with healthy participants. Methods: 223 healthy participants (68% women, 18–70 y.o., 40 mean age; 118 from France and 105 from Italy) participated in the study. Sensory-hedonic responses to four apple juice samples, spiked with four increasing concentrations of mint syrup corresponding to variations in perceived coolness, and to four chickpea cream samples, spiked with glucose-fructose syrup to modulate the perception of sweetness in contrast to the sourness induced by citric acid, were measured. Food neophobia, disgust sensitivity, sensitivity to reward and PROP (6-n-propylthiouracil) responsiveness were measured. Results: Sensory-hedonic responses to the food models were found to vary across participants and allowed to identify different groups. Two clusters were established for the apple juice differing in liking for the coolest sample: Moderate and Extreme Coolness Dislikers. Instead, three clusters were identified for the chickpea cream: 1) Sweet Likers – perceiving sweet as less intense in all samples and showing liking increments with increasing sweetness and decreasing sourness; 2) Sweet Dislikers – tended to perceive higher sweetness intensity and liking raised with increasing sourness and decreasing sweetness; 3) Inverted U-Shaped – with an optimum liking corresponding to intermediate concentrations. Clusters' differences were found in age and in sensitivity to reward, with Sweet Likers being the youngest and the most sensitive to reward. The approach allowed identifying the level of sensory properties that minimized rejection and maximized liking within and across clusters. Conclusions: The two food models will be adopted to study the effect of cancer therapy on taste perception and liking responses, for the development of tailor-made products well accepted by patients experiencing taste alterations.